2020
DOI: 10.3390/biomedicines8120562
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Systemic Expression of a Novel PD-1 Blocking Nanobody from an AAV Vector Provides Antitumor Activity without Toxicity

Abstract: Immune checkpoint blockade using monoclonal antibodies (mAbs) able to block programmed death-1 (PD-1)/PD-L1 axis represents a promising treatment for cancer. However, it requires repetitive systemic administration of high mAbs doses, often leading to adverse effects. We generated a novel nanobody against PD-1 (Nb11) able to block PD-1/PD-L1 interaction for both mouse and human molecules. Nb11 was cloned into an adeno-associated virus (AAV) vector downstream of four different promoters (CMV, CAG, EF1α, and SFFV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…Hence, a PD-1-specific scFv-Fc fusion protein was delivered by a Her2-targeted AAV vector, leading to reduced tumor growth in mouse models [111]. AAV vectors provide sustained nanobody expression both locally and systemically in preclinical models of human diseases, including solid tumors [112,113].…”
Section: Adeno-associated Viral Vectorsmentioning
confidence: 99%
“…Hence, a PD-1-specific scFv-Fc fusion protein was delivered by a Her2-targeted AAV vector, leading to reduced tumor growth in mouse models [111]. AAV vectors provide sustained nanobody expression both locally and systemically in preclinical models of human diseases, including solid tumors [112,113].…”
Section: Adeno-associated Viral Vectorsmentioning
confidence: 99%
“…To overcome these limitations, alternative strategies to produce mAbs in vivo have been widely investigated. Adeno-associated viruses (AAVs) have had a leading role in the development of gene therapy strategies aiming at the production of monoclonal antibodies for the treatment of several disorders, including cancer [35][36][37][38][39]. However, the sustained transgene expression achieved using this viral vector may not be adequate for the production of immunostimulatory monoclonal antibodies due to their often narrow therapeutic windows [40].…”
Section: Expression Of Immunostimulatory Antibody-based Moieties By Mrnamentioning
confidence: 99%
“…In fact, this approach was used by us to deliver in vivo a novel anti-PD-1 nanobody (Nb11) capable of blocking the PD-1 / PD-L1 interaction for mouse and human molecules [ 78 ]. This study showed that sustained AAV-mediated expression of the Nb11 prevented colon adenocarcinoma tumor formation in 30% of mice, significantly increasing survival without evidence of toxicity or autoimmune events.…”
Section: Aav Vectors Expressing Nanobodies For Cancer Treatmentmentioning
confidence: 99%